2012
DOI: 10.3389/fmicb.2012.00101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Activity of Denitrifiers of Chilean Arid Soil Ecosystems

Abstract: The Chilean sclerophyllous matorral is a Mediterranean semiarid ecosystem affected by erosion, with low soil fertility, and limited by nitrogen. However, limitation of resources is even more severe for desert soils such as from the Atacama Desert, one of the most extreme arid deserts on Earth. Topsoil organic matter, nitrogen and moisture content were significantly higher in the semiarid soil compared to the desert soil. Although the most significant loss of biologically preferred nitrogen from terrestrial eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The observed nosZ gene abundance was higher than nirS and nirK , whereas the nirS abundance was 0.96‐ to 3.16‐fold higher than nirK (Figure ), in agreement with Orlando, Carú, Pommerenke, and Braker (). Although the abundances of nirS and nirK genes were similar across the four sites; variations in nirS gene abundance were not responsible for the shifts in PDR.…”
Section: Discussionsupporting
confidence: 87%
“…The observed nosZ gene abundance was higher than nirS and nirK , whereas the nirS abundance was 0.96‐ to 3.16‐fold higher than nirK (Figure ), in agreement with Orlando, Carú, Pommerenke, and Braker (). Although the abundances of nirS and nirK genes were similar across the four sites; variations in nirS gene abundance were not responsible for the shifts in PDR.…”
Section: Discussionsupporting
confidence: 87%
“…Similar observations were made in soils affected by ephemeral desert bloom events in the southern limit of the desert (98). Nitrogen loss has been investigated via denitrification of nitrogen-limited desert soil (99). Use of functional gene markers for bacterial denitrifier communities (nirK, nirS) allowed detection of only nirK-type denitrifier genotypes, and it was concluded that these genotypes are predominantly dormant and stable over long periods but may become active when conditions become favorable for denitrification.…”
Section: Molecular Biologymentioning
confidence: 64%
“…Even though it is not possible to be certain that all the minima of a PES have been found, the use of a variant of the rarefaction plot [20][21][22][23] provides an estimate on how many seeds should be minimized to obtain, if not all, at least most of the minima for a particular PES. We use the words "global minimum" as the established one, but do not exclude the possibility that a lower one can eventually be found.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22][23] In applying it to our case, we plot the number of different local minima N LM as a function of the number of seeds N s that are explored. To make some progress in that direction, we borrow from ecology the concept of rarefaction.…”
Section: Number Of Local Minimamentioning
confidence: 99%